A Polymer Network Prepared by the Thiol‐yne Photocrosslinking of a Liquid Crystalline Dendrimer. Issue 6 (16th January 2013) - Cervera‐Procas, Ramón; Sánchez‐Somolinos, Carlos; Serrano, José L.; Omenat, Ana
Abstract A polymer network is prepared by the thiol‐yne photopolymerization of multifunctional dendrimer with a tetrathiol crosslinker. The network obtained shows a liquid crystalline phase at room temperature, which has been characterized by optical microscopy, differential scanning calorimetry, and X‐ray diffraction. Photoinduced deformation of uniaxially aligned free‐standing films of the photocrosslinked material has been demonstrated.